The Performance of Indonesian Citizen Character and its Contributors of Senior High School Students in Sleman Yogyakarta Indonesia - Istiningsih, Istiningsih (International Journal of Engineering and Technology, 2018)
Character education is as a current issue in Indonesia. Ministry of Education, ministry of Social Welfare care about character. The movement of building the character are designed through schools, community organization, higher or university institution. Research about character is interesting in Indonesia. Some research about it have already done. They described the character as mental that are belonging by someone. The research that try to classify the character based on the place where the person perform it, is seldom to be done. This research focused on Indonesian citizen character. There is very close relation between environment and the character. Inside the effort to build the character is education. Essentially, education is a condition. So the task of education is to design the conducive environment. This research studied deeply about the environments that surely effect the character building. The study was done for high school students in Sleman Yogyakarta Indonesia. The data was collected by questionnaire for students that were taken randomly. The result of data analysis was confirmed with observation. The result shows that family environment is the biggest in contributing character building of students. The students perform very good character of patriotism when they were at family environment; respect the national flag and patriotism when they were at school; against disintegration when they were at community, and respect all religions when they were at the self-environment. The students performed little bit low of character of against disintegration when they were at family environment; possess Pancasila attitude and love towards the nation when they were at school; respect national song when they were at community; and patriotism when they were at the self-environment. The environment that is low in character building should be empowered, in contrary the potential place should be paid attention.Â